"Second Life" of Abandoned Temples – Retrospect and Prospects. Issue 11 (February 2019) - Uscinowicz, Jerzy
Abstract: This paper presents "second life" of abandoned Christian temples. It focuses on searching for modern methods of saving the architecture of temples from ruination and profanation, while ensuring its dignified transformation. It presents selected examples of full or partial reconstructions of the ruins of temples and interconfessional conversions in the last quarter of a century in Poland. It also shows the process of transformation of spatial and functional structures as well as iconography of the temples, implemented throughout adaptation, modernization or extension. It covers problems in architectural conservation as well as essential ideological aspects of symbolical and liturgical nature. Apart from a retrospective look at first post-war buildings of this type there are also latest author projects introduced. They exemplify a design method of a "non-invasive" approach to historical monuments, including respect for their historical values and adding new qualities at the same time. Those examples are representative for the architecture of cultural borderland, which attempts to synthesize both Western and Eastern Christian art.